The Methodology of Najmuddin Sulaiman ath-Thufi: Its Application, and Implications in the Commentary on the Hadith of the Establishment of Maslahah from the Book At-Ta'yin Syarh Al-Arba'in An-Nawawiyah - Muchammad Chajar Ashqolani; Nur Hannan; Muhammad Royyan Faqih Azhary; Edi Massholihin (BAMALA Institute, 2026)
This study examines the hadith commentary methodology of Sheikh Najmuddin Sulaiman ath-Thufi in the book at-Ta'yin Syarh al-Arba'in an-Nawawiyah, focusing on hadith number 6 (on dubious matters) and number 32 (on la dharara wa la dhirara). The objectives of this research are to analyze ath-Thufi's methodology, its application in hadith commentary, and the implications of his thought. This research employs a library research method with a qualitative approach. The primary data source is ath-Thufi's at-Ta'yin, while secondary sources include books on hadith commentary, ushul fiqh, biographical dictionaries (tarajim), and relevant academic journals. The findings indicate that ath-Thufi's methodology tends toward al-Manhaj al-Ijmali al-Ushuli, a global method that is concise in linguistic and chain of transmission aspects but profoundly detailed in ushul fiqh discourse, although its application is inconsistent. The core theory constructed by ath-Thufi is that ri'ayah al-mashlahah (the preservation of public interest) is stronger than nash (sacred text) and ijma' (consensus), thus it must take precedence in matters of muamalah and customs, while the domain of worship remains under the authority of nash and ijma'. The implications of this theory include the emergence of legal dualism and social criticism of sectarian fanaticism. This study concludes that ath-Thufi's thought makes a significant contribution to the development of maqashid asy-syari'ah theory, despite sparking controversy among ushul fiqh scholars.